The Effect of Domestic Violence (KDRT) on the Level of Harmony in the Family - Rahmayanti Rahmayanti; Ismaidar Ismaidar (RIRAI Publisher, 2023)
The family is the littlest unit of society comprising of the head of the family and a few individuals who are assembled and live in one put beneath a roof in a state of interdependency. Problem formulation how the influence of Domestic Violence (KDRT) on the level of harmony in the family. In married life, both for husband and wife, children and family members, as well as the community to get a sense of security, and be free from all forms of violence that are harmful to themselves and to others, and which can cause trauma or fear for those who others because of treatment by means of violence, which is not in accordance with the philosophy of Pancasila and the 1945 Constitution of the Republic of Indonesia. 23 of 2004 concerning the Elimination of Domestic Violence.The purpose of this research is to find outthe effect of Domestic Violence (KDRT) on harmony in the family and ways to anticipate the occurrence of domestic violence (Domestic Violence).This research uses descriptive analytical research method, the approach used is normative juridical. The approach method used in this research is the statutory approach.